(untitled) - J D. K Wilson (Rome, 1999)
The book is divided into two major sections: The first discusses changes in operational techniques rather than changes in technology; the second presents information of relevance to vessel operators who are either considering the construction of a new vessel or overhauling and re-equipping an existing vessel.
Keywords: fisheries - economic aspects